W line shape in the resistively detected nuclear magnetic resonance. (18th June 2015) - Desrat, W; Piot, B A; Maude, D K; Wasilewski, Z R; Henini, M; Airey, R
Abstract: The resistively detected nuclear magnetic resonance (RDNMR) performed on a two-dimensional electron gas is known to exhibit a peculiar 'dispersive' line shape at some filling factors, especially around . Here, we study in detail the inversion of the dispersive line shape as a function of the filling factor from to . The RDNMR spectra show a new characteristic W line shape in the longitudinal resistance, whereas dispersive lines detected in the Hall resistance remain unchanged. This W resonance, like the dispersive line, can be fitted correctly by a model of two independent response functions, which are the signatures of polarized and unpolarized electronic sub-systems.